Case Method Learning in Economic Education: A Way to Enhance Academic Achievement - Andi Tenri Ampa; Andi Annisa Sulolipu (Jurnal Pendidikan Ekonomi, 2024)
The purpose of this study was to determine whether student learning achievement increases with the case method learning paradigm. The data were collected using using a questionnaire distributed through Google Form. Furthermore, the data was processed using regression analysis. A total of 188 active students of the Economics Education Study Program, Makassar State University were used as samples for this study, selected based on considerable factors. The results showed that the consistency value of the learning achievement variable and indicated that learning achievement has been increased with the involvement of case method learning paradigm. The results of this study support the theory that the use of the case method learning model can improve student learning achievement. The results of this study provide a significant influence on the efforts of educators and institutions to improve student learning outcomes and teaching quality by using more interactive and collaborative teaching methods. Keywords: learning model, case method, learning achievement